Dynamic Price Competition with Price Adjustment Costs and Product Differentiation - Gianluigi Vernasca (Fondazione Eni Enrico Mattei (FEEM), 2003)
We study a discrete time dynamic game of price competition with spatially differentiated products and price adjustment costs. We characterise the Markov perfect and the open-loop equilibrium of our game. We find that in the steady state Markov perfect equilibrium, given the presence of adjustment costs, equilibrium prices are always higher than prices at the repeated static Nash solution, even though, adjustment costs are not paid in steady state. This is due to intertemporal strategic complementarity in the strategies of the firms and from the fact that the cost of adjusting prices adds credibility to high price equilibrium strategies. On the other hand, the stationary open-loop equilibrium coincides always with the static solution. Furthermore, in contrast to continuous time games, we show that the stationary Markov perfect equilibrium converges to the static Nash equilibrium when adjustment costs tend to zero. Moreover, we obtain the same convergence result when adjustment costs tend to infinity.
Keywords: C72; C73; L13; 330; Price adjustment costs; Difference game; Markov perfect equilibrium; Open-loop equilibrium; Preiswettbewerb; Anpassungskosten; Produktdifferenzierung; Dynamisches Spiel; Duopol; Theorie